Telaah Kritis Arah Baru Perkembangan Paradigma Pendidikan Agama Islam Di Indonesia Dalam Menerima Sains - Miftahudin Miftahudin (Indonesian Journal of Humanities and Social Sciences, 2022)
This article aims to find a new direction for the development of the paradigm of Islamic religious education in Indonesia in its reception of the development of Western science. This article uses a qualitative approach with the type of library research. This approach requires researchers to explore data from documents, archives, and sources in manuscripts related to the new direction of the Islamic religious education paradigm in its acceptance of secular Western science. This study found a new direction of the paradigm of Islamic religious education in accepting science. It's to the results conducted by Ian G. Barbour are integrative; the teachings of Islam in Islamic religious education can synergize with science, which is connoted as secular, in developing existing science.